eLearning Readiness of Higher Education Institutions Students during Pandemic: Domain and Gender Perspectives - Kartiwi, Mira; Gunawan, Teddy Surya; Ahmad, Robiah (IEEE, 2021)
In 2020, the pandemic has triggered a rapid paradigm shift and necessitated a prompt switch in teaching methods worldwide. This significant change has affected the educators to rethink and assess the notion of teaching and learning, as well as the impact on the students. While many have gained adequate exposure to eLearning, the prompt switch to remote learning has triggered a new set of challenges. The result of this study shows that although most students express their readiness for remote teaching and learning, the sudden shift to online mode prompted different concerns after the trial session started. Hence, the assessment of readiness may only offer a partial view of the eLearning conundrum. Furthermore, evaluation of students' experience during remote teaching and learning period shows an interesting pattern on the different perceptions of online teaching mode between male and female students and among the domain of the study. Finally, it highlights the potential support that educational institutions may provide to ease the transitions process.